PERANAN EVALUASI PROGRAM PEMBELAJARAN DALAM MENINGKATKAN KUALITAS PENDIDIKAN - Jamilah Jamilah (Institut Kariman Wirayudha Sumenep, 2013)
Effort of is make-up of the quality of education need effort of[is make-up of the quality of study because estuary from various study program which with quality. Strive the make-up of study program need information result of programs evaluation of study previous. To be able to compile better study program, result of previous program evaluation represent reference which cannot be left . Yielded information to study program and also education program here in after. If the information can give more picture of comprehenship if study program evaluation reach evaluation to quality of study covering teacher performance, study facility, class climate, student attitude and motivation learn student and assessment of student result.